Effect of Physical Effort due to Increased Intensity in Biochemical Variables in Blood and Some Basic Skills of Volleyball Players - Arif Abdul Jabbar Hussain (Journal of Global Pharma Technology, 2018)
AbstractThe object of research is to know effects of physical exercise on treadmill focused on enzymes, creatine, Phosphokinase, Cholesterol, Hemoglobin (H b), dehydrogenase (HDL) in blood and effect on performance of basic skills of volley ball. Researcher presumed existence of significant differences between before and after examinations focused on Hemoglobin (H b), Cholesterol, and Enzymes like creatine, phosphokinase (CPK), lactate dehydrogenase (HDL) in performance of some basic skills of volley ball. The tests proved differences. Total 18 persons physically suitable for the research were made to undergo in this trial. The main experiment was applied which included biochemical values before the skill test and later physical exercise by running on treadmill for 12 minutes with change in its angle of elevation, then biochemical values recorded post skill test. The result of research revealed positive effects for change in biochemical values related to this experiment and its enzymes like creatine, phosphokinase (HDL) (CPK) and at the performance of skill in volleyball like hitting ball within trial revealed said biochemical effect negative. It is also recommended in the research that biochemical tests bring traces of variation in blood within level related to each player at different level of their function.Keywords: Physical effort, Intensity, Biochemical, Blood and volleyball.